Language as cognitive tool kit: How language supports relational thought - Gentner, Dedre (The American psychologist, 2016)
The extreme version of the Whorfian hypothesis-that the language we learn determines how we view the world-has been soundly rejected by linguists and psychologists alike. However, more moderate versions of the idea that language may influence thought have garnered recent empirical support. This article defends 1 such view. I propose that language serves as a that allows us to represent and reason in ways that would be impossible without such a symbol system. I present evidence that learning and using relational language can foster relational reasoning-a core capacity of higher order cognition. In essence, language makes one smarter. (PsycINFO Database Record